2015
DOI: 10.1002/mnfr.201500067
|View full text |Cite
|
Sign up to set email alerts
|

Role of taurine in the pathogenesis of obesity

Abstract: Taurine is a sulfur-containing amino acid that is present in mammalian tissues in millimolar concentrations. Taurine is involved in a diverse array of biological and physiological functions, including bile salt conjugation, osmoregulation, membrane stabilization, calcium modulation, anti-oxidation, and immunomodulation. The prevalence of obesity and being overweight continues to rise worldwide at an alarming rate. Obesity is associated with a higher risk of metabolic and cardiovascular diseases, cancer, and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
92
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 116 publications
(204 reference statements)
2
92
0
10
Order By: Relevance
“…Ingestion of taurine has been shown to alleviate metabolic diseases such as hyperlipidemia, diabetes, hypertension and obesity in animal models. Synthetic activity and concentration of taurine in adipose tissues and plasma have been shown to decrease in humans and animals during the development of obesity, suggesting a relationship between taurine deficiency and obesity [16]. …”
mentioning
confidence: 99%
“…Ingestion of taurine has been shown to alleviate metabolic diseases such as hyperlipidemia, diabetes, hypertension and obesity in animal models. Synthetic activity and concentration of taurine in adipose tissues and plasma have been shown to decrease in humans and animals during the development of obesity, suggesting a relationship between taurine deficiency and obesity [16]. …”
mentioning
confidence: 99%
“…In addition, taurine has multiple biological effects, such as protection against liver cirrhosis and antioxidative, 27 anti-inflammatory, antiatherosclerotic, 28,29 and antiobesity effects. 30 Unfortunately, evidence that taurine supplementation reduces BP in human hypertension is inconclusive despite the fact that multiple experimental studies have demonstrated the hypotensive effect of taurine in different hypertensive animal models.The antihypertensive effect of taurine in humans has only been confirmed in a few clinical studies with small sample sizes (n=10-12) that were short term (7 days to 6 weeks). …”
mentioning
confidence: 99%
“…Taurine is involved in many physiological functions including osmoregulation, antioxidation, calcium modulation, and membrane stabilization 34) . An analysis of taurine transporter knockout mice suggests that taurine has a significant role in maintaining normal cellular function, with knockouts showing a premature aging phenotype 35) .…”
Section: Taurinementioning
confidence: 99%
“…This suggests that taurine has a similar mechanism of action as statins and adiponectin, both of which are CRM candidates. Interestingly, several studies have reported that taurine increases plasma adiponectin levels 34) . Moreover, it has been reported that taurine inhibits angiotensin II 38) , suggesting that taurine may have a similar effect as that of the ARBs.…”
Section: Taurinementioning
confidence: 99%
See 1 more Smart Citation